-35.248711306 Hope this helps:)
Answer:
x=-5, y=-2. (-5, -2).
Step-by-step explanation:
x-3y=1
-x+6y=-7
----------------
3y=-6
y=-6/3
y=-2
x-3(-2)=1
x+6=1
x=1-6
x=-5
Answer:
Solve for K by simplifying both sides of the inequality, then isolating the variable.
Inequality Form:
k > 1
<u>Interval Notation</u>:
(1, ∞)
Step-by-step explanation:
f(x) = 5x − 1 and g(x) = 2x^2 + 1
(f × g)(x) = (5x − 1)(2x^2 + 1)
(f × g)(x) = 10x^3 - 2x^2 + 5x - 1
Substitute x = - 3
(f × g)(-3) = 10(-3)^3 - 2(-3)^2 + 5(-3) - 1
(f × g)(-3) = 10(-27) - 2(9) -15 - 1
(f × g)(-3) =-270 - 18 - 16
(f × g)(-3) = -236
Answer
- 236
8 and 1
8 squared is 64 and 1 squared is 1
64 + 1 = 65
Hope this helps :)